2005
DOI: 10.1080/15287390590912153
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment For Benefits Analysis: Framework for Analysis of A Thyroid-Disrupting Chemical

Abstract: Benefit-cost analysis is of growing importance in developing policies to reduce exposures to environmental contaminants. To quantify health benefits of reduced exposures, economists generally rely on dose-response relationships estimated by risk assessors. Further, to be useful for benefits analysis, the endpoints that are quantified must be expressed as changes in incidence of illnesses or symptoms that are readily understood by and perceptible to the layperson. For most noncancer health effects and for nonli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Relevancy analysis for PCBs and propylthiouracil suggest that concordance between rodent and human modes‐of‐action depends on the life stage of exposure. There is a good degree of concordance for the developmental neurotoxicity using altered TH concentrations as a key event (Crofton & Zoeller, 2005; Zoeller & Crofton, 2005) but no concordance for the tumourigenic effects that require TSH upregulation as a key event (Axelrad et al. , 2005).…”
Section: Tdc Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevancy analysis for PCBs and propylthiouracil suggest that concordance between rodent and human modes‐of‐action depends on the life stage of exposure. There is a good degree of concordance for the developmental neurotoxicity using altered TH concentrations as a key event (Crofton & Zoeller, 2005; Zoeller & Crofton, 2005) but no concordance for the tumourigenic effects that require TSH upregulation as a key event (Axelrad et al. , 2005).…”
Section: Tdc Mixturesmentioning
confidence: 99%
“…Table 2 The chemical used in the PHAH mixture, the concentration in the highest dose of the mixture tested, the ratio of each chemical in the mixture relative to the total mixture mass and the ratio relative to TCDD (from Chemical Concentration a (lg ⁄ mL) Ratio (TCDD) Ratio (total mass) human modes-of-action depends on the life stage of exposure. There is a good degree of concordance for the developmental neurotoxicity using altered TH concentrations as a key event but no concordance for the tumourigenic effects that require TSH upregulation as a key event (Axelrad et al, 2005). Data gaps in key events have been identified that should be researched to increase confidence in the relevancy of this mode-of-action that include: a better characterization of the induciblity of and sensitivity of UGTs during human and rodent foetal development, comparative data on the relationship between serum and brain tissue levels of THs, and comparative studies on the effects of moderate and mild hypothyroxinemia on nervous system development.…”
Section: Tdc Mixturesmentioning
confidence: 99%
“…We are particularly interested in applying a Bayesian hierarchical model to quantify exposureassociated variability in relative risk represented by the exposure-response model f (d i ; β). The Hill model (9) is used as an example to demonstrate the hierarchical modeling methodology in this study and has been reparameterized as Equation (4). In this parameterization, the format of the parameter b represents the sensitivity of response and has a unit of "response/dose g ."…”
Section: Exposure-response Modelingmentioning
confidence: 99%
“…A number of researchers have attempted to develop general quantitative methods or conceptual models to describe noncancer risk probabilistically. (1)(2)(3)(4)(5) As agencies such as the U.S. Environmental Protection Agency (US EPA) move toward probabilistic risk assessment, (6)(7)(8) new methods are needed to probabilistically quantify human variability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hauger et al (2002) and Knapp et al (2003) have developed risk/cost/benefit models to evaluate wastewater treatment systems and water transfers from agricultural to urban and environmental uses. Similar models have been proposed to evaluate different agricultural practices (Osei et al 2003), forest management practices (Brown 2002), remediation of contaminated lands (Tam and Byer 2002), perform environmental impact assessments (Bojorquez‐Tapia et al 2005), and public health management programs (Axelrad et al 2005; Denman et al 2005). Taylor et al (2004) have addressed the uncertainties associated with environmental measurements taken for the purpose of characterizing contaminated lands and supporting remedy decision making and have shown how measurement errors contribute to decision errors, which can have significant financial and public‐health consequences.…”
Section: Approaches To Risk Of Remedy Evaluationmentioning
confidence: 99%